Електрофізичнi властивостi вуглець-неорганічних нанокомпозитів C/MXOY/SiO2 - Makhno, S. N.; Bogatyrov, V. M.; Bogatyrov, V. M.; Oranskaya, E. I.; Gunko, V. M.; Gorbyk, P. P.; Leboda, R.; Skubiszewska-Zieba, J. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
A comparative analysis of the characteristics C/MxOy/SiO2 materials obtained in different ways had been done. It was noted the influence of methods of preparation on the morphology, composition and, consequently, the sorption and electrochemical characteristics of the nanocomposites C/MxOy/SiO2 and C/M/SiO2. It was demonstrated the possibility of using percolation theory to predict the electrical conductivity of carbon-inorganic nanocomposites on the content of an electrically conductive component.